The genus Bilabrella Lindl. (Orchidaceae, Habenariinae): materials to the taxonomic revision - Kras, Marta; Olędrzyńska, Natalia; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2018)
The aim of the paper is to present materials to the taxonomic revision of the African orchid genus Bilabrella Lindl., based on herbarium materials, specimens conserved in FAA as well as literature. It was compiled using classical taxonomic methods. The research involved determining differences between Bilabrella and other genera of Habenariinae in Africa. Its morphological structure was analysed and key features for the generic taxonomy defined. An infrageneric classification is proposed. A full description of each species and distribution data are provided. The ecological requirements and phenology of all species have been assembled and systematized.